Five-year survival outcomes for patients with advanced melanoma treated with pembrolizumab in KEYNOTE-001. (31st January 2019) - Hamid, O; Robert, C; Daud, A; Hodi, F S; Hwu, W J; Kefford, R; Wolchok, J D; Hersey, P; Joseph, R; Weber, J S; Dronca, R; Mitchell, T C; et al.
Abstract: Background: Pembrolizumab demonstrated robust antitumor activity and safety in the phase Ib KEYNOTE-001 study (NCT01295827) of advanced melanoma. Five-year outcomes in all patients and treatment-naive patients are reported herein. Patients whose disease progressed following initial response and who received a second course of pembrolizumab were also analyzed. Patients and methods: Patients aged ≥18 years with previously treated or treatment-naive advanced/metastatic melanoma received pembrolizumab 2 mg/kg every 3 weeks, 10 mg/kg every 3 weeks, or 10 mg/kg every 2 weeks until disease progression, intolerable toxicity, or patient/investigator decision to withdraw. Kaplan–Meier estimates of overall survival (OS) and progression-free survival (PFS) were calculated. Objective response rate and PFS were based on immune-related response criteria by investigator assessment (data cut-off, September 1, 2017). Results: KEYNOTE-001 enrolled 655 patients with melanoma; median follow-up was 55 months. Estimated 5-year OS was 34% in all patients and 41% in treatment-naive patients; median OS was 23.8 months (95% CI, 20.2–30.4) and 38.6 months (95% CI, 27.2–not reached), respectively. Estimated 5-year PFS rates were 21% in all patients and 29% in treatment-naive patients; median PFS was 8.3 months (95% CI, 5.8–11.1) and 16.9 months (95% CI, 9.3–35.5), respectively. Median response duration was not reached; 73% of all responses and 82% of treatment-naive responses were ongoing at data cut-off; the longest response was ongoing at 66 months. Four patients [all with prior response of complete response (CR)] whose disease progressed during observation subsequently received second-course pembrolizumab. One patient each achieved CR and partial response (after data cut-off). Treatment-related AEs (TRAEs) occurred in 86% of patients and resulted in study discontinuation in 7.8%; 17% experienced grade 3/4 TRAE. Conclusions: This 5-year analysis of KEYNOTE-001 represents the longest follow-up for pembrolizumab to date and confirms the durable antitumor activity and tolerability of pembrolizumab in advanced melanoma. Clinical Trial Registry: ClinicalTrials.gov, NCT01295827.